A single-crystal ternary positive electrode material and an in-situ gas phase etching-coating integrated preparation method and application thereof
Patent Information
- Application Number
- CN202611333479.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-09
AI Technical Summary
目前,工业上主要采用高温固相烧结法制备该类材料,但该工艺存在固有缺陷:为获得颗粒圆润化效果需依赖高温长时保温,易导致晶粒异常长大、锂挥发损失,难以兼顾小尺寸与高倍率性能;同时,烧结产物往往发生硬团聚,需采用气流粉碎进行解聚,该过程易造成晶粒破碎与晶格畸变,破坏单晶结构完整性
本发明通过在烧结降温区间引入CO2选择性气相刻蚀,能够优先刻蚀颗粒棱角与表面粗晶层,实现颗粒圆润化,刻蚀结束后原位切换载带三甲基铝的氧气气氛,利用刻蚀后表面富含缺陷位点和原子悬挂键的高活性特征,原位生成与基底化学键合的Al2O3包覆层,钝化表面缺陷,稳定界面避免了传统独立包覆设备及多次升温返烧的弊端,工艺流程大幅缩短,生产效率显著提高,能耗与设备成本明显降低。所得材料兼具颗粒圆润、结构完整、界面稳定的综合优势,在倍率性能和循环寿命方面表现优异,能够满足高能量密度动力电池对正极材料长寿命、高安全性的应用需求。
Smart Images

Figure CN122879836A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ternary cathode material technology, and more specifically, to a single-crystal ternary cathode material and its in-situ vapor phase etching-coating integrated preparation method and application. Background Technology
[0002] Among lithium-ion battery cathode materials, single-crystal ternary cathode materials have become one of the mainstream technologies for high-energy-density power batteries due to their advantages such as the absence of grain boundary cracks, high mechanical strength, good thermal stability, and high compaction density. Currently, the high-temperature solid-state sintering method is mainly used in industry to prepare this type of material. However, this process has inherent defects: to obtain the effect of rounded particles, it is necessary to rely on high temperature and long-term heat preservation, which can easily lead to abnormal grain growth and lithium volatilization loss, making it difficult to achieve both small size and high rate performance; at the same time, the sintered products often undergo hard agglomeration, which requires airflow pulverization for deagglomeration. This process can easily cause grain breakage and lattice distortion, destroying the integrity of the single-crystal structure.
[0003] To address the aforementioned issues, previous studies have proposed introducing CO2 vapor-phase etching in the later stages of sintering. This can simultaneously achieve selective smoothing of particle edges and deagglomeration of aggregates, effectively improving morphology and dispersibility. However, while CO2 etching optimizes morphology, it also introduces numerous defect sites and dangling atomic bonds onto the particle surface. If these are not effectively passivated, the electrolyte will preferentially erode these active sites during long-term cycling, accelerating transition metal dissolution and interfacial side reactions, thus limiting high-temperature cycle life. To overcome this drawback, surface coating treatment is usually required after etching. However, existing coating technologies such as solid-phase coating, liquid-phase coating, and atomic layer deposition are all independent processes after sintering, requiring dedicated equipment and material transfer, resulting in lengthy and costly processes. Furthermore, the coating layer and substrate are mostly physically adsorbed together, resulting in weak bonding forces that are prone to peeling and failure under high-temperature conditions, failing to effectively utilize the high activity of the etched surface to achieve a strong chemically bonded interface.
[0004] Therefore, there is an urgent need to develop an integrated technology that can simultaneously complete morphology optimization, agglomeration and deagglomeration, and surface defect passivation within the same sintering process, in order to break through the current technical bottleneck of multiple performance indicators being mutually constrained. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a single-crystal ternary cathode material and its in-situ vapor phase etching-coating integrated preparation method and application. Within the same temperature window of the single-crystal sintering cooling section, rounding, depolymerization, and dealkali removal are achieved simultaneously through selective etching with low-concentration CO2. Then, organometallic vapor is introduced to generate a chemically bonded oxide coating layer in situ. The entire process is completed continuously in situ without the need for additional equipment or material transfer.
[0006] This invention is implemented as follows: In a first aspect, the present invention provides an in-situ vapor phase etching method. A method for preparing single-crystal ternary cathode material by integrated coating includes the following steps: a nickel-cobalt-based precursor and a lithium source are mixed uniformly in a certain proportion and sintered at high temperature in an oxygen atmosphere; after sintering, the temperature is lowered to 700-750℃, and an oxygen-containing mixed gas containing CO2 is introduced for isothermal etching; after etching, the temperature is kept constant, and an oxygen-containing gas carrying an organic aluminum source is introduced for in-situ gas-phase coating; after coating, the oxygen atmosphere is restored and the material is cooled and discharged, washed with water, dried, and sieved to obtain the single-crystal ternary cathode material.
[0007] In an optional embodiment, the nickel-cobalt-based precursor is selected from at least one of nickel-cobalt-manganese hydroxide and nickel-cobalt-aluminum hydroxide; And / or, the lithium source is lithium hydroxide monohydrate or lithium carbonate; And / or, the Li / Me molar ratio of the nickel-cobalt-based precursor to the lithium source is 1.03-1.08.
[0008] In an optional embodiment, the mixing is performed using a high-speed mixer with a mixing speed of 400-600 rpm and a mixing time of 10-20 min.
[0009] In an optional embodiment, the heating rate of the high-temperature sintering is 1-3℃ / min, the sintering temperature is 850-930℃, and the holding time is 8-12h.
[0010] In an optional embodiment, in the in-situ CO2 etching process, the volume fraction of CO2 in the CO2-containing oxygen-containing mixed gas is 3%-8%, the etching time is 1-2 hours, and the total gas flow rate is 0.5-1.0 m³ / s. 3 / (h·m 3 The pressure is 0-5 Pa, which is slightly positive.
[0011] In an optional embodiment, in the in-situ gas phase coating process, the organoaluminum source is trimethylaluminum, the volume fraction of trimethylaluminum in the carrier gas is 0.1%-0.5%, and the processing time is 30-60 min.
[0012] In an optional embodiment, the thickness of the alumina coating layer in the in-situ vapor phase coating process is 3-5 nm.
[0013] In an optional embodiment, the water washing temperature is 50-80℃, the solid-liquid ratio is 1:(1.5-3), and the washing time is 8-15 min; And / or, the drying is vacuum drying at a temperature of 100-120°C; And / or, the mesh size of the sieve used for sieving is 300-400 mesh.
[0014] Secondly, the present invention provides a single-crystal ternary cathode material, which is prepared by any one of the methods described in the foregoing embodiments.
[0015] Thirdly, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the active material of the positive electrode is a single-crystal ternary positive electrode material as described in the foregoing embodiments.
[0016] The present invention has the following beneficial effects: This invention introduces CO2 selective vapor-phase etching during the sintering cooling phase, which preferentially etches away the sharp edges and coarse grains on the surface of the particles, achieving particle rounding. After etching, the oxygen atmosphere carrying trimethylaluminum is switched in situ. Utilizing the highly active characteristics of the etched surface rich in defect sites and atomic dangling bonds, an Al2O3 coating layer chemically bonded to the substrate is generated in situ, passivating surface defects and stabilizing the interface. This avoids the drawbacks of traditional independent coating equipment and multiple heating and reheating processes, significantly shortening the process flow, greatly improving production efficiency, and significantly reducing energy consumption and equipment costs. The resulting material combines the advantages of rounded particles, intact structure, and stable interface, exhibiting excellent rate performance and cycle life, and meeting the application requirements of high-energy-density power batteries for long-life and high-safety cathode materials. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0018] Figure 1 This is a SEM image of the single-crystal ternary cathode material prepared in Example 1 of this invention; Figure 2 This is a SEM image of the single-crystal ternary cathode material prepared in Comparative Example 1 of this invention; Figure 3 This is a SEM image of the single-crystal ternary cathode material prepared in Comparative Example 3 of this invention. Detailed Implementation
[0019] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0020] In existing technologies, while CO2 vapor-phase etching alone in the later stages of sintering can simultaneously achieve particle rounding, agglomeration depolymerization, and reduction of residual alkali, selective etching significantly increases the density of surface defect sites and atomic dangling bonds. If not effectively passivated, the electrolyte will preferentially erode defect sites during long-term cycling, accelerating the dissolution of transition metals and the increase in interfacial impedance, thus limiting the improvement of the material's high-temperature cycle life. Traditional coating technologies (solid-phase coating, liquid-phase coating, low-temperature ALD deposition, etc.) are all independent processes after sintering, requiring additional specialized equipment and material transfer, resulting in long processes and high costs. Moreover, the coating layer and the substrate are mostly physically adsorbed together, with weak bonding forces, making them prone to detachment at high temperatures. They cannot utilize the highly active surface after etching to achieve chemical bonding, resulting in limited coating quality and stability.
[0021] To address the aforementioned issues, this invention utilizes the surface energy differences at different sites of single-crystal particles and the high reactivity of the etched interface to perform vapor phase treatment in two consecutive stages during the sintering cooling phase: first, selective CO2 etching is used to achieve edge rounding, necking depolymerization, and removal of the surface lithium-rich phase; then, a trace amount of trimethylaluminum vapor is switched in situ to form a coating layer on the etched surface, passivating defects and stabilizing the interface. Thus, morphology optimization and surface passivation are completed simultaneously in the same equipment, achieving a comprehensive improvement in material processing performance, electrochemical stability, and cycle life.
[0022] According to a first aspect of the present invention, the present invention provides an in-situ vapor phase etching method. A method for integrally coating and preparing single-crystal ternary cathode materials includes the following steps: S1. The nickel-cobalt-based precursor and the lithium source are mixed evenly in a certain proportion and sintered at high temperature in an oxygen atmosphere.
[0023] The nickel-cobalt-based precursor is selected from at least one of nickel-cobalt-manganese hydroxide and nickel-cobalt-aluminum hydroxide, preferably nickel-cobalt-manganese hydroxide; specifically, the precursor may be of type NCM523 (i.e., Ni... 0.5 Co0 .2 Mn 0.3 (OH)2), NCM622 type (Ni 0.6 Co 0.2 Mn 0.2 (OH)2), NCM811 type (Ni 0.8 Co 0.1 Mn 0.1 (OH)2), NCMA type (nickel-cobalt-manganese-aluminum quaternary hydroxide) or NCA type (nickel-cobalt-aluminum hydroxide, such as Ni) 0.8 Co 0.15 Al 0.05The precursors are any one of (OH)2, but not limited to this. All the above precursors are hydroxides prepared by co-precipitation methods known in the art. After being mixed with a lithium source and sintered at high temperature, they can respectively prepare single-crystal ternary cathode materials of the entire system, including NCM523, NCM622, NCM811, NCMA, and NCA. The preparation method of this invention has wide applicability to precursors of various systems.
[0024] In some preferred embodiments of the present invention, the lithium source is lithium hydroxide monohydrate or lithium carbonate.
[0025] Furthermore, the Li / Me molar ratio of the nickel-cobalt-based precursor to the lithium source is 1.03-1.08, for example, it can be 1.03, 1.04, 1.05, 1.06, 1.07 or 1.08, or any value in the range between the two.
[0026] In this application, the Li / Me molar ratio is defined as the ratio of the molar amount of Li in the lithium source to the molar amount of the total metal element Me in the nickel-cobalt-based precursor. Wherein, Me represents the total transition metal content in the precursor; when the nickel-cobalt-based precursor is a nickel-cobalt-manganese precursor, Me is the sum of the molar amounts of Ni, Co, and Mn; when the nickel-cobalt-based precursor is a nickel-cobalt-aluminum precursor, Me is the sum of the molar amounts of Ni, Co, and Al. In this application, the mixing is performed using a high-speed mixer with a mixing speed of 400-600 rpm, for example, 400 rpm, 500 rpm, or 600 rpm; the mixing time is 10-20 min, for example, 10 min, 15 min, or 20 min.
[0027] In some embodiments, the high-temperature sintering is carried out in an oxygen atmosphere, preferably a pure oxygen atmosphere, where oxygen maintains the stability of high-valence metal ions in the cathode material and promotes single crystal growth. Sintering is performed at a rate of 1-3℃ / min to 850-930℃, and held for 8-12 hours to complete single crystal growth and crystallization. Specifically, the sintering temperature can be adaptively adjusted according to different precursor systems: for high-nickel systems (such as NCM811, NCA, etc.), due to the high nickel content, the sintering temperature is relatively low to avoid intensified lithium-nickel mixing and excessive grain growth at high temperatures; for low-nickel systems (such as NCM523, NCM622, etc.), the sintering temperature can be increased accordingly. Through the coordinated control of the heating rate, sintering temperature, and holding time, single crystal particles with high crystallinity and uniform grain size can be obtained, while effectively suppressing lithium volatilization and the generation of lattice defects.
[0028] S2. After sintering, the temperature is lowered to 700-750℃, and a mixture of oxygen and CO2 is introduced for isothermal etching.
[0029] As an example, the temperature of the cooling section can be 710℃, 720℃, 730℃, 740℃, or 750℃, or any value in between. At this temperature, CO2 exhibits moderate reactivity, preferentially etching the edges and sintering necks of the particles to achieve rounding and deagglomeration, while avoiding excessive etching of the crystal planes and destruction of the main structure of the single crystal. This temperature range falls precisely within the sintering cooling section, allowing subsequent processing to be carried out directly using the residual heat from sintering without additional heating, effectively reducing energy consumption. Simultaneously, this temperature is well-matched with the thermal decomposition temperature window of trimethylaluminum (TMA), ensuring both sufficient TMA decomposition and chemical bonding with the active sites on the etched surface, and preventing excessively high temperatures that could lead to Al2O3 particle agglomeration or an excessively thick coating layer, thus guaranteeing the uniformity of the coating layer and interface stability.
[0030] In some embodiments, during the in-situ CO2 etching process, the volume fraction of CO2 in the CO2-containing oxygen-containing mixed gas is 3%-8%, the etching time is 1-2 hours, and the total gas flow rate is 0.5-1.0 m³ / s. 3 / (h·m 3 The pressure is 0-5 Pa, slightly positive. In this process, CO2, as a selective etching gas, utilizes the surface energy differences at different sites on the single crystal particles to preferentially react with high surface energy regions such as particle edges, protrusions, and coarse grain layers, smoothing out sharp edges and achieving particle rounding. At the same time, CO2 molecules preferentially penetrate to the sintering neck (i.e., the intergranular connection site) and react with it, causing the agglomerates to preferentially break along the sintering neck, achieving deagglomeration without external force and avoiding the mechanical damage to the single crystal structure caused by traditional airflow pulverization. In addition, CO2 also reacts with residual lithium compounds (such as Li2CO3, LiOH, etc.) on the particle surface, converting them into soluble lithium salts or gaseous products, simultaneously achieving the effect of reducing residual alkali. Oxygen, as a carrier gas, dilutes the CO2 concentration while maintaining the oxidation state of the material, preventing the loss of lattice oxygen due to the reducing properties of CO2.
[0031] As an example, the volume fraction of CO2 in the CO2-containing oxygen-containing gas mixture can be 3%, 4%, 5%, 6%, 7%, or 8%, or any value within a range of both; the total gas flow rate can be 0.5 m³ / s. 3 / (h·m 3 ), 0.6 m 3 / (h·m 3 ), 0.7 m 3 / (h·m 3 ), 0.8 m 3 / (h·m 3 ), 0.9 m 3 / (h·m 3 ) or 1.0 m 3 / (h·m 3) etc., or any range between the two.
[0032] S3. After etching is completed, keep the temperature constant and switch to in-situ vapor phase coating by introducing oxygen-containing gas carrying organic aluminum source.
[0033] In some embodiments, in the in-situ gas-phase coating process, the organoaluminum source is trimethylaluminum, and the volume fraction of trimethylaluminum in the carrier gas is 0.1%-0.5%, with a processing time of 30-60 minutes. Specifically, after CO2 etching, the temperature is kept constant (still 700-750℃), and the inlet gas is switched to oxygen carrying trace amounts of trimethylaluminum (TMA). Trimethylaluminum undergoes thermal decomposition in the oxygen atmosphere, and the released aluminum atoms or aluminum-oxygen active species react chemically with the lattice oxygen and atomic dangling bonds abundant on the surface of the etched particles, nucleating in situ and growing into a uniform Al2O3 coating layer with a thickness of 3-5 nm. This coating layer is firmly bonded to the substrate through chemical bonding (Al-O-Me bonds), rather than simple physical adsorption, thus exhibiting high bonding strength and being difficult to peel off. The byproduct methane generated in the above in-situ gas-phase coating process is discharged with the exhaust gas and is centrally combusted before being released, posing no environmental safety hazard.
[0034] As an example, the volume fraction of trimethylaluminum in the carrier gas can be 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%, or any value between the two; the thickness of the alumina coating can be 3 nm, 4 nm, or 5 nm, or any value between the two.
[0035] It should be noted that when the TMA volume fraction is too low (<0.1%) or the processing time is too short (<30 min), the coating layer is discontinuous or insufficient in thickness, making it difficult to completely seal surface defects. When the TMA volume fraction is too high (>0.5%) or the processing time is too long (>60 min), the coating layer is too thick, which increases lithium-ion diffusion resistance and is detrimental to rate performance. Controlling the TMA volume fraction within the 3-5 nm range is sufficient to completely cover surface defect sites without significantly hindering the lithium-ion insertion and extraction process.
[0036] S4. After coating, restore the oxygen atmosphere and cool down to discharge the material. After washing, drying and sieving, the single-crystal ternary cathode material is obtained.
[0037] In some preferred embodiments, the water washing temperature is 50-80°C, the solid-liquid ratio is 1:(1.5-3), and the washing time is 8-15 min, which can further remove residual soluble lithium salts and ensure surface cleanliness. Preferably, the drying is vacuum drying, and the drying temperature is 100-120℃; Preferably, the mesh size of the sieve used for sieving is 300-400 mesh.
[0038] According to a second aspect of the present invention, the present invention provides a single-crystal ternary cathode material, which is prepared by the method described in any one of the foregoing embodiments.
[0039] According to a third aspect of the present invention, the present invention provides a lithium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the active material of the positive electrode is a single-crystal ternary positive electrode material as described in the foregoing embodiments.
[0040] The features and performance of the present invention will be further described in detail below with reference to embodiments.
[0041] Example 1 This embodiment provides an in-situ vapor phase etching method. A method for integrally coating and preparing single-crystal ternary cathode materials includes the following steps: S1. Weigh NCM622 precursor and lithium hydroxide monohydrate at a Li / Me molar ratio of 1.05, add them to a high-speed mixer, and mix at 500 rpm for 15 min to obtain a uniform mixture. Load the mixture into a sagger, push it into a roller kiln, and sinter it at 900℃ under an oxygen atmosphere by heating at 3℃ / min and holding for 10 h to complete single crystal growth and crystallization. S2. After sintering, the temperature is reduced to 720℃. Then, a mixture of CO2 and oxygen with a volume fraction of 5% is introduced and etched at a constant temperature for 1.5 hours. S3. After etching, maintain a constant temperature of 720℃, switch the inlet gas to oxygen carrying 0.2% volume fraction of trimethylaluminum (TMA), and perform constant temperature coating treatment for 40 minutes. S4. Stop the TMA supply, restore the pure oxygen atmosphere, continue to cool to room temperature and then discharge the material. The material can be dispersed by gentle stirring. Wash with 70°C deionized water for 12 minutes, filter, dry and sieve to obtain single crystal ternary cathode material.
[0042] The prepared single-crystal ternary cathode material was observed using a scanning electron microscope, such as... Figure 1 As shown, the roundness of the obtained material is significantly improved, and the coating layer is uniform.
[0043] Example 2 This embodiment provides an in-situ vapor phase etching method. The method for preparing single-crystal ternary cathode materials by coating is the same as that in Example 1, except that the TMA volume fraction is adjusted to 0.1% and the coating time is 40 min during the coating stage.
[0044] Example 3 This embodiment provides an in-situ vapor phase etching method. The method for preparing single-crystal ternary cathode materials by coating is the same as that in Example 1, except that the etching temperature is adjusted to 750℃, the CO2 volume fraction is 5%, and the etching time is 1h; the coating temperature is synchronized to 750℃, the TMA volume fraction is 0.2%, and the coating time is 30min.
[0045] Comparative Example 1 This comparative example provides a method for preparing a single-crystal ternary cathode material, including the following steps: S1. Using NCM622 precursor, lithium hydroxide monohydrate was weighed at a Li / Me molar ratio of 1.05 and added to a high-speed mixer. The mixture was mixed at 500 rpm for 15 min to obtain a uniform mixture. S2. Load the mixture into a sagger, push it into a roller kiln, heat it to 900℃ at 3℃ / min under an oxygen atmosphere, hold it for 10h, and complete the single crystal growth and crystallization. S3. Then, the material is cooled and discharged. The material is a hard agglomerate, which is deagglomerated to D50≈2.7μm by industrial-grade airflow pulverization. S4, wash with 70℃ deionized water for 12 min (solid-liquid ratio 1:2), filter, vacuum dry at 120℃, and pass through a 400-mesh sieve to obtain single-crystal ternary cathode material.
[0046] The prepared single-crystal ternary cathode material was observed using a scanning electron microscope, such as... Figure 2 As shown, the prepared cathode material has no etching or in-situ coating, and the particle roundness is poor. After air jet milling, a large amount of micro powder is generated, which affects the high-temperature storage performance.
[0047] Comparative Example 2 This comparative example provides a method for preparing a single-crystal ternary cathode material, including the following steps: S1. Using NCM622 precursor, lithium hydroxide monohydrate was weighed at a Li / Me molar ratio of 1.05 and added to a high-speed mixer. The mixture was mixed at 500 rpm for 15 min to obtain a uniform mixture. S2. Load the mixture into a sagger, push it into a roller kiln, heat it to 900℃ at 3℃ / min under an oxygen atmosphere, hold it for 8~12h, and complete the single crystal growth and crystallization. S3. After high-temperature sintering, the temperature is lowered to 720℃. A mixture of CO2 and oxygen with a volume fraction of 5% is introduced and etched at a constant temperature for 1.5 hours. S4. Stop the CO2 supply, restore the pure oxygen atmosphere, continue to cool down to room temperature and discharge the material. The material is in a loose state. Gently stir to depolymerize. Wash with 70℃ deionized water for 12 minutes, filter, dry and sieve to obtain single crystal ternary cathode material.
[0048] Comparative Example 3 This comparative example provides a method for preparing a single-crystal ternary cathode material, including the following steps: S1. Using NCM622 precursor, lithium hydroxide monohydrate was weighed at a Li / Me molar ratio of 1.05 and added to a high-speed mixer. The mixture was mixed at 500 rpm for 15 min to obtain a uniform mixture. S2. Load the mixture into a sagger, push it into a roller kiln, heat it to 900℃ at 3℃ / min under an oxygen atmosphere, hold it for 8~12h, and complete the single crystal growth and crystallization. S3. After high-temperature sintering, the temperature is lowered to 720℃. A mixture of CO2 and oxygen with a volume fraction of 5% is introduced and etched at a constant temperature for 1.5 hours. S4. Stop the CO2 supply, restore the pure oxygen atmosphere, continue to cool down to room temperature and discharge the material. The material is in a loose state. Gently stir to deagglomerate. Wash with 70℃ deionized water for 12 minutes, filter, dry and sieve to obtain the etched powder. S5. Solid-phase coating: Add powder and 0.2% Al2O3 by mass to a high-speed mixer and mix at 200~400 rpm for 10~20 min to obtain coating material. Then, sinter at 700℃ again to obtain single-crystal ternary cathode material.
[0049] The prepared single-crystal ternary cathode material was observed using a scanning electron microscope, such as... Figure 3 As shown, the obtained cathode material, after etching and solid-phase coating, has a poor coating effect and uneven coating layer.
[0050] Experimental Example 1 The monocrystalline ternary cathode materials prepared in Examples 1-3 and Comparative Examples 1-3 were used to fabricate 2032 coin cells and their electrochemical performance was tested. The results are shown in Table 1. The preparation and testing methods are as follows: The preparation method of coin cell batteries includes: for lithium-ion batteries, assembly is carried out in a glove box with oxygen <0.1ppm and water content <0.1ppm, with lithium sheet as negative electrode, PE separator, electrolyte consisting of EC and DEC mixed in a volume ratio of 1:1, 1mol LiPF6 added, and assembled into 2032 type coin cell batteries.
[0051] The conditions for button cell testing include: charging voltage range of 3.0V-4.3V, charge and discharge tests at 0.1C, 1C, 5C and 10C respectively, and finally testing the 1C capacity and cycle performance at a high temperature of 45℃.
[0052] Table 1. Performance Test Results
[0053] According to the results in Table 1, Comparative Example 1, which uses a conventional high-temperature sintering followed by direct airflow milling and deagglomeration process, produces a material with a roundness of only 0.63 and a wide particle size distribution (Span=1.21). The airflow milling process generates a large amount of micro-powder and grain breakage, resulting in an initial coulombic efficiency of only 90.8% and a capacity retention of only 81.3% after 300 cycles at 1C, indicating rapid decay. This is mainly attributed to the presence of numerous angular particles and microcracks, stress cracking caused by volume changes during cycling, and continuous side reactions between the fresh fracture surface and the electrolyte. Comparative Example 2, which introduces CO2 vapor phase etching during the sintering cooling stage, improves the roundness to 0.68, allowing for deagglomeration without strong milling. The initial coulombic efficiency increases to 92.3%, and the 300-cycle retention increases to 87.5%, demonstrating the effectiveness of the etching process in optimizing morphology and reducing residual alkali. However, the surface defect sites are not effectively passivated after etching, resulting in rapid decay in the later stages of long cycles. Comparative Example 3 uses a traditional solid-phase coating process after etching, and the retention rate after 300 cycles is further improved to 89.1%. However, due to uneven solid-phase coating and the fact that the coating layer and the substrate are only physically adsorbed, it is easy to fall off locally during high-temperature cycling, resulting in limited long-term protection.
[0054] In contrast, Examples 1-3, using an integrated process of CO2 etching and TMA in-situ vapor phase coating, resulted in materials with improved roundness (0.72-0.75), narrower particle size distribution (Span = 1.02-1.07), uniform and dense in-situ coating layer with high bonding strength through Al-O-Me chemical bonding to the substrate. The initial coulombic efficiency reached 92.2%-92.7%, and the capacity retention after 300 cycles at 1C reached 90.3%-92.1%. Example 1 showed the best performance, achieving a 92.1% capacity retention after 300 cycles with an average weekly decay rate of only 0.026%, approximately 58% lower than that of Comparative Example 1.
[0055] In summary, this invention employs an integrated process of "high-temperature selective etching + isothermal in-situ chemical bonding coating" to achieve synergistic optimization of morphology and interface: CO2 selective etching eliminates particle sharp edges, achieving non-pulverized deagglomeration and transforming the material from a sharp-edged, hard agglomerate requiring pulverization into a highly rounded, highly dispersed, and undamaged state; then, relying on the highly active surface obtained by etching, a uniform Al2O3 coating layer is grown in-situ, which is firmly anchored to the substrate surface by chemical bonding, solving the problems of poor adhesion and easy detachment of traditional coatings, ultimately endowing the material with excellent rate performance and long cycle life.
[0056] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. An in-situ vapor phase etching method A method for preparing single-crystal ternary cathode materials by integrated coating, characterized in that, Includes the following steps: The nickel-cobalt-based precursor and the lithium source were mixed evenly in a certain proportion and then sintered at high temperature in an oxygen atmosphere. After sintering, the temperature is lowered to 700-750℃, and a mixture of oxygen and CO2 is introduced for isothermal etching. After etching, the temperature is kept constant, and oxygen-containing gas carrying organic aluminum source is introduced for in-situ gas phase coating. After coating, the oxygen atmosphere is restored and the material is cooled and discharged. After washing, drying and sieving, single crystal ternary cathode material is obtained.
2. The method according to claim 1, characterized in that, The nickel-cobalt-based precursor is selected from at least one of nickel-cobalt-manganese hydroxide and nickel-cobalt-aluminum hydroxide; And / or, the lithium source is lithium hydroxide monohydrate or lithium carbonate; And / or, the Li / Me molar ratio of the nickel-cobalt-based precursor to the lithium source is 1.03-1.
08.
3. The method according to claim 1, characterized in that, The mixing is performed using a high-speed mixer with a mixing speed of 400-600 rpm and a mixing time of 10-20 min.
4. The method according to claim 1, characterized in that, The heating rate for the high-temperature sintering is 1-3℃ / min, the sintering temperature is 850-930℃, and the holding time is 8-12h.
5. The method according to claim 1, characterized in that, In the in-situ CO2 etching process, the volume fraction of CO2 in the CO2-containing oxygen-containing mixed gas is 3%-8%, the etching time is 1-2 hours, and the total gas flow rate is 0.5-1.0 m³ / s. 3 / (h·m 3 The pressure is 0-5 Pa, which is slightly positive.
6. The method according to claim 1, characterized in that, In the in-situ gas phase coating process, the organoaluminum source is trimethylaluminum, the volume fraction of trimethylaluminum in the carrier gas is 0.1%-0.5%, and the processing time is 30-60 min.
7. The method according to claim 1, characterized in that, In the in-situ vapor phase coating process, the thickness of the alumina coating layer is 3-5 nm.
8. The method according to claim 1, characterized in that, The water washing temperature is 50-80℃, the solid-liquid ratio is 1:(1.5-3), and the washing time is 8-15 min; And / or, the drying is vacuum drying at a temperature of 100-120°C; And / or, the mesh size of the sieve used for sieving is 300-400 mesh.
9. A single-crystal ternary cathode material, characterized in that, Prepared by the method according to any one of claims 1-8.
10. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the active material of the positive electrode is the single-crystal ternary positive electrode material as described in claim 9.